KOMUNITAS BASIS GEREJAWI SEBAGAI SALAH SATU WADAH SOSIALISASI SEMANGAT PERSAUDARAAN UNIVERSAL ENSIKLIK FRATELLI TUTTI DI PAROKI MARIA BUNDA PEMBANTU ABADI, BATAM - Sitepu, Mitsiebenson; Moa, Antonius; Antono, Yustinus Slamet (UNIKA Santo Thomas, 2025)
As small faith-based communities, Basic Ecclesial Communities (BECs) play a strategic role in fostering bonds of solidarity, dialogue, and compassion toward others, transcending ethnic, cultural, and religious boundaries, core principles promoted in Fratelli Tutti. In the context of MBPA Parish, BECs function not only as spaces for communal faith gatherings but also as arenas for faith formation and the cultivation of social awareness. The methodology employed in this study combines both library research and fieldwork. Data were collected through literature review involving books, articles, and journals relevant to the research theme, as well as through field interviews conducted. The data were analyzed by interpreting the interview findings in light of the principles and values of universal fraternity as articulated in Fratelli Tutti. The findings reveal that BECs in MBPA Parish serve as both a means of faith formation and a locus for social praxis. Through regular meetings, social outreach, and engagement with the broader community, BECs reinforce values of solidarity, care for the marginalized, and foster spaces for intergroup dialogue. However, the research also identifies several challenges, both internal and external. Internal challenges include the limited realization of dialogue, openness, and shared responsibility among BEC members in daily life. External challenges manifest in societal stigma and negative perceptions toward Catholics by other groups. The study concludes that BECs, when guided by a vision aligned with the spirit of Fratelli Tutti, have the potential to be effective instruments for the socialization of universal fraternity, embodied in dialogue, openness, and shared responsibility. Continuous and consistent socialization processes may ultimately contribute to social transformation toward a more just, peaceful, and fraternal world.